Ectopic Pregnancy Following Interval Tubal Sterilization - Shrestha, Deepak; Baniya, Sebina; Regmi, Sudeep (Journal of Lumbini Medical College, 2017)
Introduction: Tubal sterilization is a highly effective method of permanent contraception. However, pregnancy can still occur following a successful procedure. Published literatures report a failure rate of 0.13-1.3% and 15-33% of such pregnancies are likely to be ectopic. Case report: A 33 years para three lady with prior history of tubal ligation presented with generalized abdominal pain and several episodes of vomiting. Bimanual examination revealed a soft and mobile mass of 2 x 3 cm in right adnexa. Urine pregnancy test was positive and ultrasonogram showed a heterogeneous mass of 3.4 x 3.3 cm in right adnexa with empty uterine cavity. Culdocentesis resulted in aspiration of frank non-clotting blood. She then underwent emergency laparotomy with bilateral salpingectomy for ruptured ectopic pregnancy. Conclusion: Ectopic pregnancy after tubal sterilization though rare is not entirely impossible. All women who are offered this procedure should always be educated about its failure rate. And in women presenting with acute abdomen, a prior history of tubal sterilization doesn’t preclude the possibility of ectopic pregnancy.